Challenges and Potential for Ovarian Preservation with SERMs. Issue 5 (1st May 2015) - Ting, Alison Y.; Petroff, Brian K.
Abstract: Tamoxifen (TAM) is a selective estrogen receptor modulator with tissue-specific effects on estrogen signaling used predominantly for treatment and chemoprevention of breast cancers. Recent studies have shown that TAM prevents infertility and decreases follicular loss from common cancer chemotherapy and radiation therapy in preclinical models. Here we review current and novel uses of selective estrogen receptor modulator s and advantages and challenges for translation of TAM for human fertility preservation.